Comparative studies of mitochondrial proteomics reveal an intimate protein network of male sterility in wheat (Triticum aestivum L.) - Wang, Shuping (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.